Hubungan Karakteristik, Beban Kerja, dan Pertanggungjawaban dengan Motivasi Perawat dalam Pelaksanaan Pendokumentasian Asuhan Keperawatan di RSUD Raden Mattaher Jambi Tahun 2013 - Imran, Suryadi (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2014)
ABSTRACT Background : Nurse characteristic,workload and nurse accountability in documentations, constitute factors that regards to motivate nurses in performance of upbringing nurse care documentations. The subject of the reserch is to find efects, to be known factors which is mostly engaged nurse motivation in upbringing the caring  of nurse documents. Methods : This research design is focused on analitic description with the approach of cross sectional method. Its purpose is to describe  the relation  among nurse characteristic, workload, and liability with nurse motivation in performing caring nurse documentations and influenced factors. In Raden Mattaher General Hospital. The numbers of the responden in this research consists of 112 executor nurses. Results : The observation in finding dominant atmost factors is mostly engaged  nurse motivation as marital status and workload, with p value = 0,46 (OR 3.242), for marital status and p value = 0,049 (OR 2.306) for workload. Its meaning that variable marital status and nurse workload made by predictors to motivate nurse in upbringing  nurse caring documents. Conclusion : Recomendation of this researh in nurses’ motivation in performing documentation is more optimized by system repair, empowerment nurse via increasing education, training about upbringing to good and right care of increasing s nurse motivation in performing the nurse documentation of caring.   Keyword: Charachteristic, Workload, Accountability, Motivation.